THE EFFECT OF CURRENT RATIO, QUICK RATIO, DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO AND RETURN ON EQUITY ON FIRM VALUE (A study on property companies listed on the Indonesia Stock Exchange from 2014 to 2020) - Khairunisa, Marista; Putri, Laras Sahrinaz; Mulia, Sofan; Prakoso, Iqbal Budi; Novayani, Okta; Arnan, Sendi Gusnandar (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine The Effect of Current Ratio, Quick Ratio, Debt to Asset Ratio, Debt to Equity Ratio and Return on Equity On Firm Value in property sector companies listed on the Indonesia stock exchange in the period 2014 to 2020. The sample in this study was 64 financial statements from 10 companies. The research method used in this research is descriptive and explanatory methods. The sampling technique used in this study was non probability sampling with a purposive sampling method. Analysis of the data used in this study is a panel data regression analysis at a significance level of 5%. The program used in analyzing data using SPSS v 20. The results showed that Current Ratio Affects firm value but Quick Ratio, Debt to Asset Ratio, Debt to Equity Ratio and Return on Equity have no affects firm value.